Companions or patients? The impact of family presence in genetic consultations for inherited breast cancer: Relational autonomy in practice. (30th July 2018) - Gilbar, Roy; Barnoy, Sivia
Abstract: As in other areas of medical practice, relatives accompany patients to genetic consultations. However, unlike in other areas, the consultations may be relevant to the relatives' health because they may be at risk of developing the same genetic condition as the patient. The presence of relatives in genetic consultation may affect the decision‐making process and it raises questions about the perception of patient autonomy and the way it is practiced in genetics. However, these issues have not been examined in previous empirical studies. This article aims to fill this gap by reporting findings from a qualitative study with clinicians working in the area of inherited breast cancer. The findings indicate that family presence has an impact on the patient's decisions to undergo genetic testing and preventative operations when she is diagnosed as a carrier. The findings further indicate that, unlike in other areas of medical practice, blood relatives who are present in consultations are perceived by clinicians as patients or potential patients, and this in turn increases their involvement in discussions in the consultation room. Finally, the findings indicate that in genetics, a relational approach to autonomy is applied. Decisions are made in a social context, where the relatives' views are heard and taken into account. The findings suggest that the conventional bioethical approach to autonomy, which perceives the decision‐making unit as comprising a clinician and an individual patient, is challenged in genetics. The findings thus suggest that bioethicists, lawyers and policy‐makers should consider whether this individualistic approach is still valid and applicable.